Liquid filter media

JP7633062B2Active Publication Date: 2025-02-19TEJIN FIBERS LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021057011
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-30
Publication Date
2025-02-19
Estimated Expiration
2041-03-30

AI Technical Summary

Benefits of technology

【0008】 本発明によれば、高粘性流体を通液した際の圧力損失が小さく、かつ異物の除去性能に優れた液体フィルター用濾材を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007633062000001
    Figure 0007633062000001
Patent Text Reader

Abstract

To provide a filter medium for a liquid filter, which makes a pressure loss small when a highly viscous fluid passes through it and which is excellent in foreign matter removal performance.SOLUTION: A filter medium for a liquid filter has a multilayer structure that includes a liquid inflow-side filter medium layer, an intermediate filter medium layer and a liquid outflow-side filter medium layer in this order. All the filter medium layers are made of a wet nonwoven fabric. In the filter medium for the liquid filter, an average pore diameter of the wet nonwoven fabric of the intermediate filter medium layer is smaller than an average pore diameter of the wet nonwoven fabric of the liquid inflow-side and liquid outflow-side filter medium layers.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a filter medium for a liquid filter. [Background technology]

[0002] In the semiconductor / electronics and chemical fields, there has been a demand for a technology that can effectively remove foreign matter contained in liquids during the production of highly viscous liquid products. Spunbonded nonwoven fabrics and meltblown nonwoven fabrics made of organic fibers have typically been used to filter such highly viscous liquids (for example, JP 2018-126721 A).

[0003] In the midst of this, with the miniaturization of devices and the thinning of coatings and films, it has become necessary to remove even smaller foreign objects from highly viscous liquids. However, conventional filter media designed for highly viscous liquids have large pores and are therefore unable to adequately remove these tiny foreign objects.

[0004] In order to reduce the pore size, methods have been considered in which spunbonded nonwoven fabrics or meltblown nonwoven fabrics are subjected to a calendaring process to consolidate them, or meltblown nonwoven fabrics are layered to increase the collection rate. However, these methods lack uniformity in the pore size obtained, so the thickness of the filter material must be increased to maintain the filtration accuracy, and there is a concern that the filtration resistance will increase. In addition, foreign matter passes through large pores, and the friction between the filtrate and the filter material increases during the liquid passage, increasing the pressure loss (for example, Patent No. 6560101). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2018-126721 A [Patent Document 2] Patent No. 6560101 Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide a filter medium for liquid filters which has a small pressure loss when a highly viscous fluid is passed through it and has excellent foreign matter removal performance. [Means for solving the problem]

[0007] That is, the present invention is a filter material for liquid filters having a multilayer structure including a liquid inlet side filter material layer, an intermediate filter material layer, and a liquid outlet side filter material layer in this order, all of the filter material layers being made of wet nonwoven fabrics, and characterized in that the average pore size of the wet nonwoven fabric of the intermediate filter material layer is smaller than the average pore size of the wet nonwoven fabrics of the liquid inlet side filter material layer and the liquid outlet side filter material layer. Effect of the Invention

[0008] According to the present invention, it is possible to provide a filter medium for liquid filters which has a small pressure loss when a highly viscous fluid is passed through it and has excellent foreign matter removal performance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, an embodiment of the present invention will be described in detail.

[0010] [Layer structure of filter material] The filter medium for liquid filters of the present invention has a multi-layer structure including a liquid inlet side filter medium layer, an intermediate filter medium layer, and a liquid outlet side filter medium layer in this order. The filter material for a liquid filter of the present invention comprises a liquid inlet side filter material layer, an intermediate filter material layer and a liquid outlet side filter material layer. If the filter medium includes a structure including the above-mentioned layers in this order, the filter medium may have a multi-layer structure including other layers. The total number of layers, including the liquid inlet side filter medium layer, the intermediate filter medium layer, and the liquid outlet side filter medium layer, is, for example, 3 to 10 layers.

[0011] In the liquid filter medium of the present invention, all filter layers are made of wetlaid nonwoven fabrics, and the average pore size of the wetlaid nonwoven fabric of the intermediate filter layer is smaller than the average pore size of the wetlaid nonwoven fabrics of the liquid inlet side filter layer and the liquid outlet side filter layer.

[0012] In the present invention, by using wet nonwoven fabric, compared with conventional spunbond nonwoven fabric or meltblown nonwoven fabric, it can form a structure with uniform pore size, and although its basis weight and thickness are small, it has high filtration accuracy due to its small pore size.In addition, in conventional filter material for liquid filter, the average pore size of each laminated filter material is made to be inclined from the inlet side to the outlet side, so that the dust removal rate is improved.At this time, the load is concentrated on the outermost layer of the outlet side, which has the largest friction resistance against high viscous fluid, and the void of the outermost layer filter material of the outlet side cannot be maintained, and the pressure loss during filtration may increase.This problem does not occur in the present invention.

[0013] In addition, in conventional filter media for liquid filters, a method of stacking 10 or more layers of filter media is generally used to improve filtration accuracy, but if the number of filter media is 10 or more layers and the total thickness of the filter media is 2.5 mm or more, the increase in friction with the filtrate increases the filtration resistance and the decrease in throughput, and furthermore, a sufficient filtration area cannot be obtained during filter cartridge processing, and the pressure of the filtrate cannot be dispersed, so the load is concentrated on the filter media, leading to compression in the thickness direction of the filter media. This problem does not occur in the present invention.

[0014] In the filter material for liquid filters of the present invention, the average pore size of each of the stacked filter materials decreases from the inlet side to the outlet side and then has a gradient in the direction of increasing again, so that the filter material with the larger average pore size stacked on the outlet side of the filter material with the smallest average pore size acts as a buffer material and provides shape support, thereby maintaining the voids in the filter material with the smallest average pore size and resulting in a gradual increase in pressure loss during processing of highly viscous fluids.

[0015] Furthermore, in the filter material for liquid filters of the present invention, the average pore size decreases from the inlet side to the outlet side, and then increases again, thereby making it possible to recapture foreign matter that would be initially captured by the filter material with the smallest average pore size and then pushed out, thereby improving foreign matter removal properties.

[0016] [Thickness, basis weight, air permeability] The filter medium for liquid filters of the present invention preferably has a total thickness of 1.6 to 2.5 mm, from the viewpoints of maintaining filtration accuracy and processability into a cartridge type. The thickness of each layer that constitutes the filter medium is preferably 0.1 mm or more. If the thickness of each layer is less than 0.1 mm, the filter medium needs to be compacted in order to maintain the foreign matter collection ability, which is undesirable because it may increase the pressure loss when high viscosity fluid is passed through.

[0017] In the present invention, the total number of layers is 3 or more, and the filter medium has a thickness of 1.6-2.5mm, and each layer has a small and uniform pore size, so that it can maintain high filtration accuracy, has low filtration resistance, and can obtain a high processing capacity as a filter medium.Furthermore, in the present invention, the thickness of the filter medium is small, so that the filter medium area that can be stored in the cartridge can be increased.

[0018] The filter medium for liquid filters of the present invention preferably has a total basis weight of 250 to 450 g / m from the viewpoint of reducing the liquid resistance while sufficiently collecting foreign matter inside the filter medium. 2 and stacking In order to prevent local clogging and a decrease in collection rate in each layer of the filter medium, the basis weight of each layer is preferably 15 to 90 g / m 2 It is. The filter medium for liquid filters of the present invention preferably has a Gurley air permeability of 4.5 (100 cc / sec) or less, from the viewpoint of reducing the flow resistance of highly viscous liquids.

[0019] [Layer Density] In the liquid filter medium of the present invention, the density of each layer is preferably 0.05 to 0.7 g / cm 3 The density is 0.05g / cm 3 If the density is less than 0.7 g / cm, the handling property may become poor, which is not preferable. 3 If the amount exceeds this range, it may become difficult to obtain a high filtration throughput, which is undesirable.

[0020] [Preferred embodiment of intralayer structure] In the filter medium for liquid filters of the present invention, the liquid inlet side filter layer, the intermediate filter layer and the liquid outlet side filter layer preferably all contain nanofibers with an average fiber diameter of 1000 nm or less and binder fibers with an average fiber diameter of 15 μm or less.

[0021] By including nanofibers with an average fiber diameter of 1000 nm or less in all layers, it is possible to obtain a filter medium for liquid filters that has low pressure loss when passing a highly viscous fluid and has excellent foreign matter removal performance.

[0022] In all layers of the liquid inlet side filter layer, the intermediate filter layer and the liquid outlet side filter layer, the nanofibers having an average fiber diameter of 1000 nm or less preferably account for 7 to 60% by weight. In each layer, it is preferable that the nanofibers having an average fiber diameter of 1000 nm or less and the binder fibers having an average fiber diameter of 15 μm or less are further contained, and the total of the nanofibers having an average fiber diameter of 1000 nm or less and the binder fibers having an average fiber diameter of 15 μm or less is 100% by weight.

[0023] [Nanofiber shape] The nanofibers in the present invention preferably have an average fiber diameter of 1000 nm or less, more preferably 200 to 800 nm. This fiber diameter is the single fiber diameter of the nanofibers. If the average fiber diameter exceeds 1000 nm, the filtration efficiency may decrease, which is not preferable. On the other hand, if the average fiber diameter is less than 200 nm, the porosity in the filter medium may decrease, which is not preferable, as the filtration throughput may decrease.

[0024] The average fiber diameter can be measured by taking a cross-sectional photograph of a single fiber at a magnification of 30,000 times using a transmission electron microscope (TEM). In a TEM with a length measurement function, the measurement can be performed using the length measurement function. In a TEM without a length measurement function, the photograph can be enlarged and copied, and the diameter can be measured with a ruler after taking into account the scale.

[0025] When the cross-sectional shape of a single fiber is an irregular cross-section other than a circular cross-section, the diameter of the circumscribing circle of the cross-section of the single fiber is used as the fiber diameter for calculating the average fiber diameter.

[0026] The average fiber length of the nanofiber is preferably 0.4 to 1.5 mm. If the average fiber length is less than 0.4 mm, the processability may decrease, which is not preferable. On the other hand, if the average fiber length exceeds 1.5 mm, the dispersion may be poor, resulting in agglomerated fiber masses, which may decrease the filtration efficiency and strength, which is not preferable. The ratio L / D of the average fiber length L to the average fiber diameter D is preferably 200 to 4,000, and more preferably 800 to 2,500, from the viewpoint of dispersibility in water during papermaking.

[0027] [Nanofiber material] The polymer constituting the nanofiber is, for example, polyester, polyphenylene sulfide, polypropylene, polyethylene, or polyamide. The nanofibers are preferably made of polyester, polyamide or polypropylene.

[0028] When polyester fibers are used as nanofibers, polyethylene terephthalate, polytrimethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, or copolymers having these as main repeating units with aromatic dicarboxylic acids such as isophthalic acid and 5-sulfoisophthalic acid metal salt, aliphatic dicarboxylic acids such as adipic acid and sebacic acid, hydroxycarboxylic acid condensates such as ε-caprolactone, or glycol components such as diethylene glycol, trimethylene glycol, tetramethylene glycol, hexamethylene glycol, etc. are preferred. The polyester fibers may be any of drawn, undrawn, and semi-drawn yarns.

[0029] When using polyphenylene sulfide fiber, the polyarylene sulfide forming it may have, as its constituent unit, for example, p-phenylene sulfide unit, m-phenylene sulfide unit, o-phenylene sulfide unit, phenylene sulfone unit, phenylene sulfide ketone unit, phenylene sulfide ether unit, diphenylene sulfide unit, phenylene sulfide unit containing a substituent, or phenylene sulfide unit containing a branched structure. Among them, it is preferable to have p-phenylene sulfide unit of 70 mol% or more, more preferably 90 mol% or more, and particularly poly(p-phenylene sulfide). The polyphenylene sulfide fiber may be any of drawn yarn, undrawn yarn, and semi-drawn yarn.

[0030] [Nanofiber content] In the liquid filter medium of the present invention, the content of nanofibers having an average fiber diameter of 1000 nm or less is preferably 7-60% by weight, and the content of binder fibers having an average fiber diameter of 15 μm or less is preferably 93-40% by weight in all layers of the liquid inlet side filter medium layer, the intermediate filter medium layer, and the liquid outlet side filter medium layer. The average fiber diameter of the binder fibers is preferably 2-15 μm, more preferably 3-13 μm, from the viewpoint of optimizing the pore diameter of the filter medium.

[0031] If a filter medium is made only of nanofibers, it has low compression resistance and is likely to be crushed during processing. In the present invention, by mixing binder fibers that are thicker than the nanofibers, a filter medium with high porosity and excellent compressive strength can be obtained.

[0032] When treating highly viscous fluids, it is essential to maintain the pores in the nonwoven fabric during treatment. When highly viscous fluids pass through the filter media, friction with the filter media fibers is very large, so if the pores in the filter media cannot be maintained and the fluid becomes compacted, the throughput drops significantly and pressure loss increases.

[0033] In the present invention, a multi-layered filter material for liquid filters includes a liquid inlet side filter layer, an intermediate filter material layer, and a liquid outlet side filter material layer in this order, all of the filter material layers being made of wet nonwoven fabric, and the average pore size of the wet nonwoven fabric of the intermediate filter material layer is smaller than the average pore size of the wet nonwoven fabric of the liquid inlet side filter material layer and the liquid outlet side filter material layer. This configuration allows the gaps between the fibers of the filter material to be maintained when a fluid flows in, and reduces an increase in pressure loss during processing.

[0034] [Binder fiber] The binder fiber is a thermally adhesive fiber. By including the binder fiber in the filtration layer, the strength of the nonwoven fabric, the network structure, and the bulkiness due to shrinkage can be improved. The average fiber length of the binder fibers is preferably 3 to 10 mm, from the viewpoint of providing sufficient bonding points between binders to stabilize the strength of the filter medium and eliminating disturbance of the filter medium. An undrawn yarn can be used as the binder fiber. In this case, the undrawn yarn is preferably an undrawn polyester fiber spun at a spinning speed of 600 to 1500 m / min.

[0035] Examples of the polyester include polyethylene terephthalate, polytrimethylene terephthalate, and polybutylene terephthalate. From the viewpoints of productivity, dispersibility in water, and the like, polyethylene terephthalate or copolymerized polyethylene terephthalate is preferred.

[0036] Conjugate fibers can also be used as binder fibers. As the conjugate fibers, core-sheath type conjugate fibers are preferred in which a polymer component that exhibits a fusion adhesion effect depending on the dryer temperature during papermaking, such as a non-crystalline copolyester, is arranged in the sheath, and another polymer having a melting point 20°C or more higher than these polymers is arranged in the core. These may be in the form of eccentric core-sheath type conjugate fibers or side-by-side type conjugate fibers. In terms of cost, it is preferred to use terephthalic acid, isophthalic acid, ethylene glycol, and diethylene glycol as the main components of the non-crystalline copolyester.

[0037] [Additives] The liquid inlet side filter layer, the intermediate filter layer and the liquid outlet side filter layer may further contain a fiber material that helps disperse the nanofibers and contributes to improving the porosity. This fiber material is a non-binder fiber and has a larger fineness than the nanofibers in the present invention. As this fibrous material, polyester fiber with an average fiber diameter of 2 to 15 μm is preferable.

[0038] Furthermore, the fiber material used for paper may contain, for example, wood pulp, natural pulp, synthetic pulp mainly composed of aramid or polyethylene, synthetic fibers or semi-synthetic fibers containing components such as nylon, acrylic, vinylon, and rayon.

[0039] 〔cartridge〕 In the filter material for liquid filters of the present invention, the filter material is preferably of a cartridge type. According to the present invention, a cartridge type liquid filter using the filter material for liquid filters is further provided. The shape of the cartridge type liquid filter is preferably cylindrical, and the filter material for liquid filters of the present invention is preferably arranged in a cylindrical and pleated shape between the core material of the innermost layer and the protector of the outermost layer. The folding pitch of the pleats (the distance between the peaks and valleys) is preferably 5 to 30 mm. The diameter of the core material is preferably 10 to 200 mm.

[0040] [Method for producing nanofibers] Nanofibers can be produced, for example, by the methods disclosed in WO 2005 / 095686 and WO 2008 / 130019.

[0041] That is, the islands-in-sea type composite fiber can be produced by preparing an islands-in-sea type composite fiber composed of island components made of a fiber-forming thermoplastic polymer and a sea component made of a polymer (hereinafter referred to as a "soluble polymer") that is more easily soluble in an alkaline aqueous solution than the fiber-forming thermoplastic polymer, and then subjecting the composite fiber to an alkaline weight reduction treatment using an alkaline aqueous solution to dissolve and remove the soluble polymer of the sea component from the fibers of the fiber-forming thermoplastic polymer of the island components.

[0042] The dissolution rate ratio of the easily soluble polymer of the sea part to the fiber-forming thermoplastic polymer of the island parts is preferably 200 or more, more preferably 300 to 3000. This dissolution rate ratio is preferable because it facilitates separation of the sea part and the island parts.

[0043] In the islands-in-sea type composite fiber, the melt viscosity ratio (sea / island) of the polymer of the sea component to the polymer of the island components is preferably 1.1 to 2.0, more preferably 1.3 to 1.5. If this ratio is less than 1.1, the island components tend to bond to each other during melt spinning, which is not preferred, while if it exceeds 2.0, the viscosity difference is too large and the spinning condition tends to decrease, which is not preferred. The number of island components in the cross section of the islands-in-sea type composite fiber, ie, the island number, is, for example, 100 or more, and further, for example, 500-2000.

[0044] The weight ratio of the sea part to the island parts in the islands-in-sea type composite fiber is preferably 20:80 to 80:20. This range is preferable because the thickness of the sea part between the island parts can be thinned, the sea part can be easily dissolved and removed, and the island parts can be easily converted into nanofibers. If the sea part exceeds 80% by weight, the thickness of the sea part becomes too thick, while if it is less than 20% by weight, the amount of the sea part becomes too small, and bonding between the island parts and the other island parts adjacent to it is likely to occur, which is undesirable.

[0045] As a spinneret used in melt spinning to spin islands-in-sea type composite fibers, one having a group of hollow pins or a group of fine holes (pinless) for forming island components can be used. For example, a spinneret can be used that merges the flow of island components extruded from hollow pins or fine holes with the flow of a sea component, the flow path of which is designed to fill the gaps between them, and compresses the resulting mixture to form an islands-in-sea cross section. The extruded islands-in-sea type composite fiber is solidified by cooling air and taken up by a rotating roller or an ejector set at a predetermined take-up speed to obtain an undrawn yarn. The take-up speed is preferably 200 to 5000 m / min. If it is less than 200 m / min, the productivity may decrease, which is not preferable. On the other hand, if it exceeds 5000 m / min, the stability of spinning may decrease, which is not preferable.

[0046] The obtained islands-in-sea type composite fiber is subjected to an alkali weight reduction treatment in which the sea part is dissolved and the island part is left as fiber, and the fiber remaining after the alkali weight reduction treatment is cut to a predetermined fiber length to obtain the nanofiber used in the present invention. This cutting can be performed by bundling a tow into, for example, 100,000 to 10 million fibers, or further, for example, 1 to 1 million fibers, using a guillotine cutter or a rotary cutter. The cutting to the predetermined fiber length may be performed before the alkali weight reduction treatment.

[0047] [Alkaline loss] In the above-mentioned alkali weight reduction treatment, the islands-in-sea type composite fiber is preferably 0.1 to 5% by weight, more preferably 0.4 to 3% by weight, based on the weight of the alkali solution. If it is less than 0.1% by weight, it is undesirable that drainage after the alkali weight reduction treatment becomes difficult. On the other hand, if it exceeds 5% by weight, it is undesirable that the fibers remaining as island components during the alkali weight reduction treatment may be entangled with each other.

[0048] The time for the alkali weight reduction treatment is preferably 5 to 60 minutes, more preferably 10 to 30 minutes. If it is less than 5 minutes, the alkali weight reduction may be insufficient, which is not preferable. On the other hand, if it exceeds 60 minutes, even the island components to be left as fibers may be dissolved, which is not preferable.

[0049] The alkali concentration of the aqueous alkali solution used in the alkali weight reduction treatment is preferably 2 to 10% by weight. If it is less than 2% by weight, the alkali may be insufficient, which may cause the weight reduction rate to become extremely slow, which is not preferred. On the other hand, if it exceeds 10% by weight, the alkali weight reduction may proceed too quickly, which may cause the island components to be reduced, which is not preferred.

[0050] After the alkali weight reduction treatment, in order to improve the dispersibility of the island component fibers, it is preferable to apply a dispersant to the surface of the island component fibers. The amount of the dispersant attached is, for example, 0.1 to 5.0% by weight based on the weight of the island component fibers.

[0051] [Method of producing wet-laid nonwoven fabric] In terms of filtration efficiency, it is preferable that each layer constituting the filter medium for liquid filters of the present invention is made of a wetlaid nonwoven fabric.

[0052] A method for producing a wetlaid nonwoven fabric can be, for example, to make paper using a fourdrinier paper machine, short wire paper machine, or cylinder paper machine, and then heat-treat the paper to thermally bond the nanofibers and binder fibers. The heat treatment can be carried out using, for example, a Yankee dryer or an air-through dryer after the papermaking process.

[0053] After the heat treatment, the film may be calendered or embossed, for example, using a metal roller / metal roller, a metal roller / paper roller, or a metal roller / elastic roller.

[0054] Each layer constituting the filter material for liquid filters of the present invention may be wet-laid and then laminated, or the filter material for liquid filters of the present invention may be produced by multi-layer papermaking. EXAMPLES

[0055] Examples and Comparative Examples of the present invention will be described in detail. The measurement items in the examples were measured by the following methods. "Weight %" may be abbreviated as "wt%".

[0056] (1) Average fiber diameter A transmission electron microscope (TEM) (with length measurement function) was used to take a cross-sectional photograph of the fiber at a magnification of 30,000 times, and the fiber diameter was measured using the diameter of the circumscribed circle in the cross section of a single fiber (average value of n=5).

[0057] (2) Average fiber length The ultrafine short fibers (short fibers A) before dissolving and removing the sea component were laid on a substrate and the fiber length L was measured at 20 to 500 magnifications using a scanning electron microscope (SEM) (average value for n=5). At that time, the fiber length L was measured using the length measurement function of the SEM.

[0058] (3) Eye count The basis weight was measured based on JIS P8124 (method of measuring the metric basis weight of paper).

[0059] (4) Average thickness The thickness was measured based on JIS P8118 (Method of measuring thickness and density of paper and paperboard). The measurement load was 75g / cm 2 Measurements were made at n=5 and the average value was calculated.

[0060] (5) Gurley air permeability The test was carried out based on JIS P8117 (Testing method for air permeability of paper and paperboard).

[0061] (6) Melt Viscosity The polymer after drying was set in an orifice set at the ruder temperature during spinning, and kept molten for 5 minutes. After that, it was extruded under several load levels, and the shear rate and melt viscosity at that time were plotted. Based on that data, a shear rate-melt viscosity curve was created, and the melt viscosity curve for a shear rate of 1000 sec -1 The melt viscosity was read at this time.

[0062] (7) Average pore diameter Measurements were taken using a Perm Porometer manufactured by PMI.

[0063] (8) Viscosity The viscosity was read at a rotation speed of 3 rpm using a viscometer manufactured by Toki Sangyo Co., Ltd.

[0064] (9) Pressure loss when passing high viscosity fluid A 0.6 wt% aqueous solution of carboxymethylcellulose was prepared and the entire amount was filtered through a cartridge fitted with a filter medium at a flow rate of 12 L / min, and the pressure difference between the primary and secondary sides was measured.

[0065] (10) 1μm initial collection rate An aqueous dispersion of 0.3 ppm Air Cloeaneer Test Dust (AC Fine 2 Dust) was prepared and the entire amount was filtered through a cartridge fitted with a filter medium at a flow rate of 10 L / min. The number of particles before and after filtration was measured every minute from the start until the third minute, and the average collection rate up to the third minute was calculated.

[0066] Example 1 Using polyethylene terephthalate as the island component and a polyethylene terephthalate copolymer in which polyethylene glycol was copolymerized at 4% by weight per total diol component and 5-sodium sulfoisophthalic acid was copolymerized at 9% by mole per total dicarboxylic acid component as the sea component, a sea:island composite undrawn yarn with a sea:island ratio of 30:70 (weight ratio) and the number of islands = 836 was melt spun at a spinning temperature of 290°C and a spinning speed of 1500 m / min, and once wound up to obtain an undrawn yarn. The obtained undrawn yarn was roller-drawn at a draw ratio of 4.0 times, then heat-set at 180°C, and wound up as an islands-in-sea composite drawn yarn. This was cut to a fiber length of 0.5 mm (average fiber length 0.5 mm) and reduced in weight with alkali to obtain nanofiber A with an average fiber diameter of 700 nm and an average fiber length of 0.5 mm. Further, similarly, nanofiber A' with an average fiber diameter of 400 nm and an average fiber length of 0.5 mm was obtained.

[0067] (First layer: wet-laid nonwoven fabric) A slurry was prepared by mixing nanofibers A at 7% by weight based on the total weight of the nonwoven fabric, polyethylene terephthalate fibers (non-binder fibers B) with a fineness of 1.7 dtex (average fiber diameter 12.6 μm) × fiber length of 5 mm (average fiber length 5 mm) and low-melting-point polyethylene terephthalate copolymer fibers (binder fibers C, melting point 110°C) with a fineness of 1.7 to 2.2 dtex (average fiber diameter 12.6 to 14.4 μm) at 93% by weight, and nanofibers A and binder fibers A were mixed to a total of 100% by weight. The weight ratio of non-binder fibers B to binder fibers C was 68:32.

[0068] The slurry was made by adding and dispersing a dispersant and an antifoaming agent, and the slurry was wet-laid and dehydrated with a nip roller, and then wound up. The slurry was then introduced into a belt dryer while being unwound, and a network was formed between the binder fibers by heat shrinkage to fix the structure, and the slurry was then wound up with a certain tension to obtain a wet-laid nonwoven fabric. The weights of the dispersant and the antifoaming agent were 1 to 5 parts by weight and 10 to 20 parts by weight, respectively, relative to 100 parts by weight of the total weight of the nanofibers A, the non-binder fibers B, and the binder fibers C.

[0069] (2nd to 5th layers: wet-laid nonwoven fabric) The second to fifth layers of wetlaid nonwoven fabrics were produced in the same manner as the first layer of wetlaid nonwoven fabric, except that the second layer was formulated with 10% by weight of nanofiber A, the third layer was formulated with 30% by weight of nanofiber A, the fourth layer was formulated with 40% by weight of nanofiber A, and the fifth layer was formulated with 15% by weight of nanofiber A', and the amounts of non-binder fiber B and binder fiber C were formulated so that the total amount with the nanofibers was 100% by weight.

[0070] (Laminated) The wet nonwoven fabrics prepared by the above method were laminated from the inlet side to the fifth layer in order of the filter medium with the smallest weight ratio of nanofiber A. Then, the first to fourth wet nonwoven fabric layers were laminated in the reverse order to obtain a filter medium consisting of a total of nine wet nonwoven fabric layers. The average pore size of the obtained filter medium gradually decreased from the first layer to the fifth layer on the inflow side, and then increased again from the fifth layer to the ninth layer on the outflow side.

[0071] The filter media weight is 383g / m 2 The filter had a thickness of 1.9 mm and a Gurley air permeability of 4.00. When an aqueous solution of carboxymethylcellulose (hereafter abbreviated as "CMC") with a viscosity of 400 mPa s was passed through the filter medium at a flow rate of 12 L / min, the pressure loss was 0.13 MPa, and the 1 μm particle removal rate of AC Fine Dust was 99.79%. The evaluation results are shown in Table 1.

[0072] Comparative Example 1 The same procedure as in Example 1 was carried out except that in the first to fifth layers in Example 1, the number of layers of the third layer was increased to two and the number of layers of the fourth layer was increased to three, so that the first to fifth layers were configured as eight layers in total. The average pore size of the obtained filter medium had a gradient that gradually decreased from the inlet side to the outlet side. The weight of the filter medium was 292 g / m 2 The filter had a thickness of 1.7 mm and a Gurley air permeability of 3.79. When a CMC aqueous solution with a viscosity of 400 mPa s was passed through the filter medium at a flow rate of 12 L / min, the pressure loss was 0.15 MPa and the removal rate of 1 μm particles of AC Fine Dust was 99.85%. The evaluation results are shown in Table 1.

[0073] Comparative Example 2 The nanofiber A was changed to polypropylene with a fiber length of 700 nm and a fiber length of 0.5 mm (average fiber length of 0.5 μm), and the binder fiber C was changed to a core-sheath type composite fiber with a fineness of 0.8 dtex (average fiber diameter 10.1 μm) and a fiber length of 5 mm (average fiber length 5 mm), the core part being polypropylene and the sheath part being polyethylene. The nanofiber A was gradually increased to 10 to 60% by weight relative to the weight of the filter medium, and the nanofiber A and the binder fiber C were mixed so that the total amount was 100% by weight to prepare a slurry. Then, a filter medium was obtained by wet papermaking in the same manner as in Example 1. The obtained filter medium was laminated from the inlet side to the fifth layer in order of the filter medium with the smallest weight ratio of nanofiber A. The average pore size of the filter medium obtained by lamination had a gradient that gradually decreased from the inlet side to the outlet side. In addition, the basis weight of the filter medium obtained by lamination was 300 g / m 2 The filter had a thickness of 1.6 mm and a Gurley air permeability of 4.30. When a CMC aqueous solution with a viscosity of 400 mPa s was passed through the filter at a flow rate of 12 L / min, the pressure loss was 0.18 MPa and the removal rate of 1 μm particles of AC Fine Dust was 99.55%. The evaluation results are shown in Table 1.

[0074] Comparative Example 3 A filter medium was obtained by laminating commercially available melt-blown nonwoven fabrics with different average pore sizes. The weight of the obtained filter medium was 349 g / m 2 The filter had a thickness of 1.7 mm and a Gurley air permeability of 4.62. When a CMC aqueous solution with a viscosity of 400 mPa s was passed through the filter at a flow rate of 12 L / min, the pressure loss was 0.18 MPa and the removal rate of 1 μm particles of AC Fine Dust was 99.40%. The evaluation results are shown in Table 1.

[0075] Comparative Example 4 A commercially available melt-blown nonwoven fabric was laminated to obtain a filter medium. The weight of the obtained filter medium was 483 g / m 2 The filter had a thickness of 3.5 mm and a Gurley air permeability of 4.26. When a CMC aqueous solution with a viscosity of 400 mPa s was passed through the filter at a flow rate of 12 L / min, the pressure loss was 0.27 MPa and the removal rate of 1 μm particles of AC Fine Dust was 97.90%. The evaluation results are shown in Table 1.

[0076] [Table 1]

[0077] The results are explained below. Example 1 showed a good result in that the pressure loss was 0.13 MPa when a CMC aqueous solution with a viscosity of 400 mPa s was passed through at a flow rate of 2 L / min, while the removal rate of 1 μm particles was a high collection rate of 99.79%.

[0078] Comparative Example 1 has a structure in which the pore size is tapered from the inlet side to the outlet side, and the removal rate of 1 μm particles was generally good at over 99.55%. However, because the average pore size of each layer of the laminated filter media only tapered from the inlet side to the outlet side, the pressure loss was large at 0.15 when a CMC viscosity of 400 mPa s was passed through at a flow rate of 12 L / min, even though the Gurley air permeability of the entire layer was smaller than that of Example 1.

[0079] Similarly, in Comparative Example 2, the filter material only had a gradient in which the average pore size of each layered filter material decreased from the inlet side to the outlet side, and therefore the pressure loss was large at 0.18 when a liquid with a CMC viscosity of 400 kPa s was passed through at a flow rate of 12 L / min.

[0080] In Comparative Example 3, the pore size was small because it was a melt-blown nonwoven fabric, and the Gurley air permeability of the entire layer was large at 4.62. As a result, the pressure loss when an aqueous CMC solution with a viscosity of 400 mPa s was passed through it at a flow rate of 12 L / min was high at 0.15 MPa.

[0081] In Comparative Example 4, 16 layers of filter media with an average pore size of 5 μm were laminated, the thickness was 3.5 mm, and the basis weight was 483 g / m 2By using a thick filter medium, the Gurley air permeability was reduced to 4.26, below 4.5, while improving the particle removal rate, but the pressure loss was even higher at 0.27 when a 5000mPa·s CMC aqueous solution was passed through it at a flow rate of 2L / min, and the removal rate of 1μm particles was only 97.9%. In the case of melt-blown nonwoven fabric, the pore size is nonuniform, so compaction and multiple layering of filter medium are performed to improve the filtration accuracy, but this increases the Gurley air permeability value and increases the resistance when passing high viscous fluids. On the other hand, in the case of a filter medium using nanofibers, the pore size is uniform, so the thickness is thin, and even though the Gurley air permeability is low, it has a high collection rate, and because the thickness is small, the distance over which friction occurs when passing high viscous fluids is short, so the pressure loss can be reduced. In addition, since the average pore size of each stacked filter medium becomes smaller from the inlet side to the outlet side and then has a gradient in the direction of increasing again, the filter medium with a larger average pore size on the outlet side acts as a support, thereby reducing pressure loss when a highly viscous fluid is passed through. [Industrial Applicability]

[0082] The filter material for liquid filters of the present invention can be used as a filter for filtering liquid. In particular, it can be used in the product manufacturing process in the food, beverage, pharmaceutical and electronics industries. In particular, it is suitable as a filter (depth filter) for filtering foreign matter in highly viscous liquid.

Claims

1. A filter material for liquid filters having a multi-layer structure including a liquid inlet side filter material layer, an intermediate filter material layer, and a liquid outlet side filter material layer in this order, wherein the liquid inlet side filter material layer, the intermediate filter material layer, and the liquid outlet side filter material layer all include nanofibers having an average fiber diameter of 1000 nm or less and binder fibers having an average fiber diameter of 15 μm or less, all of the filter material layers are made of wet nonwoven fabrics, and the average pore size of the wet nonwoven fabric of the intermediate filter material layer is smaller than the average pore size of the wet nonwoven fabrics of the liquid inlet side filter material layer and the liquid outlet side filter material layer.

2. Total thickness is 1.6 to 2.5 mm, total basis weight is 250 to 450 g / m 2 The filter medium for liquid filters according to claim 1,

3. 3. The filter material for liquid filters according to claim 1 or 2, which has a Gurley air permeability of 4.5 (100 cc / sec) or less.

4. 2. The liquid filter medium according to claim 1, wherein the nanofibers are made of polyester, polyamide or polypropylene.

5. The liquid filter material according to any one of claims 1 to 4, wherein the nanofiber content is 7 to 60% by weight and the binder fiber content is 10 to 90% by weight in each of the liquid inlet side filter material layer, the intermediate filter material layer and the liquid outlet side filter material layer.

6. A cartridge type liquid filter using the filter material for liquid filters according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Battery separator and manufacture thereof

    JP1997223492A

  • Method for producing nonwoven fabric

    JP2006089872A

  • Fuel filter material, manufacturing method therefor, and gasoline filter

    JP2017170352A

  • filter

    JP2018126721A

  • Filter medium for immersion type filter cartridge, and immersion type filter cartridge

    JP2018192420A